Information Technology and Knowledge Management in Evidence-based Medicine: Scoping Review - Edmond C. Kungwalo; Chipo Kanjo; Patrick A. Chikumba (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
Information technology (IT) and knowledge management (KM) are critical to evidence-based medicine (EBM). This scoping review synthesizes evidence from 17 selected articles out of 2,063 retrieved across ScienceDirect, Scopus, PubMed, and Web of Science databases to evaluate how IT and KM enhance EBM. The findings reveal two primary research streams indicating that IT and KM significantly improve patient outcomes, organizational performance, and healthcare worker job satisfaction. However, most healthcare IT projects remain program-specific, focusing heavily on disease monitoring rather than fostering collaboration and KM. Furthermore, literature lacks insight into how information system design affects healthcare delivery, and comprehensive frameworks for evaluating KM practices remain scarce.